2022
DOI: 10.35848/1347-4065/ac18a9
|View full text |Cite
|
Sign up to set email alerts
|

Ce concentration dependence of optical and scintillation properties on Ce-doped La2Si2O7 crystal

Abstract: A lanthanum pyrosilicate (La2Si2O7, LaPS) single crystal is successfully grown with a Ce-doped concentration of 0.5 to 20.0% as well as undoped LaPS for reference. The photoluminescence emission map of Ce-doped LaPS has broad emission at 360–410 nm from Ce3+ 5d-4f transition, with a decay time of 20–24 ns. In the scintillation properties, Ce-doped LaPS presents the scintillation peak at 390 nm under X-ray excitation, with the decay time constant at 26–31 ns plus another decay constant caused by the emission fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Lanthanum pyrosilicate (La 2 Si 2 O 7 , LaPS) is one of the pyrosilicate group materials. In a recent study, when doped with Ce, the LaPS showed interesting scintillation characteristics such as a medium scintillation light yield of 5400 ph/MeV with low afterglow of 30 ppm and fast scintillation decay time of 26 ns [27]. The combination of the newly discovered LaPS host with the fast Pr 3+ is expected to deliver interesting scintillation properties in both fast decay time and high scintillation light yield.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanum pyrosilicate (La 2 Si 2 O 7 , LaPS) is one of the pyrosilicate group materials. In a recent study, when doped with Ce, the LaPS showed interesting scintillation characteristics such as a medium scintillation light yield of 5400 ph/MeV with low afterglow of 30 ppm and fast scintillation decay time of 26 ns [27]. The combination of the newly discovered LaPS host with the fast Pr 3+ is expected to deliver interesting scintillation properties in both fast decay time and high scintillation light yield.…”
Section: Introductionmentioning
confidence: 99%
“…A special pulse area setup has recently been developed for scintillators with ms decay time, using which a light yield of 23000 ph/MeV for Tb-doped Sr 2 Gd 8 (SiO 4 ) 6 O 2 was reported. (33) This study is the combination of the newly discovered pyrosilicate, LaPS single crystals (34,35) with Tb as a luminescence center. This is the first report on the Tb concentration dependence of both the photoluminescence (PL) and scintillation properties of Tb-doped LaPS single crystals.…”
Section: Introductionmentioning
confidence: 99%